Efeitos do ibandronato de sódio na consolidação de fraturas femorais de ratos tratados com haste intramedular - Cavalcante, Julio César Chagas e (2011)
The Ibandronate sodium is a drug used for clinical treatment of osteoporosis and for anti-catabolic action and cause osteoclast apoptosis, an important cell responsible for bone remodeling, it was hypothesized an effect on fractures in the consolidation phase of callus remodeling.The aim of this study was to evaluate the effect of ibandronate sodium in the fracture of femurs of rats subjected to intramedullary fixation. This study used 48 adult male rats, Wistar, with the average weight of 336.63 g. All animals underwent surgery for intramedullary osteosynthesis of the right femur and subsequently performed a standardized fracture. They were divided into two groups: the ibandronate, which was administered a single dose of 15mg/kg by gavage and the control group was administered a single dose of 1.0 ml of 0.9% saline by gavage also on the same day of the procedure surgery. At 7, 14, 28 and 42 days postoperatively six animals from each group were euthanized and the femurs were subjected to X-ray study to analyze the optical density and area of callus and histological study, using samples stained with picrosirius red and analyzed under polarized light, to quantify the density of collagen type I and type III in the cortical region near the fracture and callus. The radiographs showed that the area of the callus showed no statistically significant differences between groups control and ibandronate, but in the intragroup analysis 28 and 42, the callus was significantly higher on day 7 in both groups. The optical density of intergroup evaluation showed that ibandronate group at day 42, showed a higher density than the control group. In the study of collagen in the callus, the density of type I collagen seen in the ibandronate group was higher than that observed in the control group on days 7 and 14, since the density of type III collagen found in the ibandronate group was lower than in the 7 days Control group. In the study of collagen in the cortex, collagen type I in the ibandronate group was significantly greater on day 7 than the control group and type III collagen in the ibandronate group was lower than the Control group. The results are consistent enough to say that this drug has an effect on bone fracture healing by increasing the density of type I collagen in the early stages of consolidation.